2020
DOI: 10.3390/su12062312
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a Smartphone Accelerometer for Measuring Lift Velocity in Bench-Press Exercises

Abstract: The aim of this study was to determine the validity and reliability that a smartphone accelerometer (ACC) used by a mobile basic program (MBP) can provide to measure the mean velocity of a bench-press (BP) lift. Ten volunteers participated in the study (age 23.1 ± 2.5 years; mean ± SD). They had more than one year of resistance training experience in BP exercise. All performed three attempts with different loads: 70%, 90%, and 100% of the estimated value of the one-repetition maximum (1RM). In each repetition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Characteristics of the included studies can be found in Table 3 . The apps presented in the included articles were compared with motion a capture system [ 40 , 61 , 68 , 69 ], linear encoder and transducers [ 56 , 59 , 60 , 62 , 63 , 64 , 71 ], as well as with contact platforms [ 37 , 39 , 41 , 57 , 61 , 62 , 63 , 66 ], accelerometers [ 59 , 62 , 63 , 68 , 70 ], and time photocells [ 55 , 65 , 67 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics of the included studies can be found in Table 3 . The apps presented in the included articles were compared with motion a capture system [ 40 , 61 , 68 , 69 ], linear encoder and transducers [ 56 , 59 , 60 , 62 , 63 , 64 , 71 ], as well as with contact platforms [ 37 , 39 , 41 , 57 , 61 , 62 , 63 , 66 ], accelerometers [ 59 , 62 , 63 , 68 , 70 ], and time photocells [ 55 , 65 , 67 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, [ 39 , 53 , 56 , 59 , 62 , 63 , 64 ] tested the bench press, [ 64 , 68 ] the back squat, [ 60 ] the half squat and full squat [ 39 , 53 ], [ 40 ] the snatch, [ 53 ] the hip thrust, [ 68 ] the power clean, [ 37 , 41 , 57 , 61 , 66 , 71 ] the vertical jump (CMJ, SJ or DJ), [ 58 ] the running, [ 65 , 67 ] the sprint or agility [ 55 , 70 ] the static and dynamic arm swing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations